The procedures and methods of assessment of construction works loss for Takaful in Malaysia - Mohd Fauzi, Puteri Nur Farah Naadia; Abdul Rashid, Khairuddin (International Islamic University Malaysia, 2013)
In the practice of insurance works in the Malaysian construction industry, the Contractor’s All Risk (CAR) policy is essential which specify details of construction works, insurance coverage, risks, losses and compensation entitled for the insured upon the occurrence of insurable risks. Despite the practice of insurance contract for construction in Malaysia where standard policy and agreement is been applied and used by the parties, the practice of insurance assessment for compensation and reimbursement of construction works loss specifically under construction works in Contractor’s All Risks (CAR) Takaful policy is based and relied on custom company-based or in-house reports by the experts which are the loss adjusters. The review of this study provided comprehensive understanding of loss assessment for construction works and revealed the lack of standardized industry practice on the takaful assessment for construction work loss due to absence of reliable and published framework. Hence, this study attempts to review and identify current practice in assessing construction works loss under takaful specifically for insurance of works under a Contractor’s All Risk (CAR) Takaful policy. Variety of methods and approaches used by insurers in making assessment for construction works loss for takaful are identified through literature review and content analysis. This paper is expected to produce a summary of the takaful claim and compensation focusing on the methods of assessment for construction works loss through synthesis and synchronization based on the content analysis conducted. The outcome of the study suggest that further research is required in order to develop a standard framework of takaful claim and compensation focusing on the methods of assessment for construction works loss specifically under works insurance in Contractor’s All Risks (CAR) Takaful policies.